Naming as one of pricing factors in the field of house construction on the example of housing estates in Moscow and Moscow region - E. Yu. Vasilyeva; M. G. Daniyelyan (Vestnik MGSU)
Introduction. The authors of the paper studied the issue of competition in the modern Russian market of the residential real estate. A little-studied aspect — the choice of the lexical means and forms contributing to better sales — is studied.Materials and methods. Works of domestic and foreign authors, as well as the content from official websites, prospects, outdoor advertizing and information from some of the largest developers operating in Moscow and Moscow region were considered as the materials of the research. The authors used such methods as observation, description, poll, quantitative statistical analysis, comparative analysis, structural analysis, semantic-stylistic analysis, frequency analysis, etc.Results. The authors studied the influence of language image on pricing and popularity among buyers in the market of the residential real estate. The analysis of offers of the largest developers operating in Moscow and Moscow region confirmed the assumption that the best sales, as well as the formation of higher prices, are promoted by the use of foreign words in the names of housing estates, foreign loan words to denote rooms and spaces (“lounge zone”, “play-hub”, co-working), epithets like “club house”, etc.Conclusions. As the result of the conducted research, the authors made the conclusion, that language images in names, in the description and advertizing of housing estates are an effective instrument to increase their competitiveness, better market promotion and profitable sales at higher prices. The idea that there is also a downside to this phenomenon and it is put forward as a debatable point: the language image, which forms an image of the housing estate as elite, closed, accessible only to a narrow circle of residents, and at the same time self-sufficient, providing them not only with housing, but also with a wide range of social and domestic services and even business space, leads to isolation and some kind of enclave in such complexes. Nowadays there is an a desocialization of the residents of housing estates, spreading a lifestyle that does not involve unnecessary contacts in the “outside world”, and in fact, that means the formation of a new paradigm in housing construction and a new urban philosophy.